The effect of eccentricity on visual motion prediction in peripheral vision - Riku Hirano; Kosuke Numasawa; Yusei Yoshimura; Takeshi Miyamoto; Tomohiro Kizuka; Seiji Ono (Physiological Reports, 2023)
Abstract The purpose of the current study was to clarify the effect of eccentricity on visual motion prediction using a time‐to‐contact (TTC) task. TTC indicates the predictive ability to accurately estimate the time‐to‐contact of a moving object based on visual motion perception. We also measured motion reaction time (motion RT) as an indicator of the speed of visual motion perception. The TTC task was to press a button when the moving target would arrive at the stationary goal. In the occluded condition, the target dot was occluded 500 ms before the time to contact. The motion RT task was to press a button as soon as the target moved. The visual targets were randomly presented at five different eccentricities (4°, 6°, 8°, 10°, 12°) and moved on a circular trajectory at a constant tangent velocity (8°/s) to keep the eccentricity constant. Our results showed that TTC in the occluded condition showed an earlier response as the eccentricity increased. Furthermore, the motion RT became longer as the eccentricity increased. Therefore, it is most likely that a slower speed perception in peripheral vision delays the perceived speed of motion onset and leads to an earlier response in the TTC task.